PAR2 induces ovarian cancer cell motility by merging three signalling pathways to transactivate EGFR. (30th December 2020) - Jiang, Yuhong; Lim, Junxian; Wu, Kai‐Chen; Xu, Weijun; Suen, Jacky Y.; Fairlie, David P.
Abstract : Background and Purpose: Specific cellular functions mediated by GPCRs are often associated with signalling through a particular G protein or β‐arrestin. Here, we examine signalling through a GPCR, protease‐activated receptor 2 (PAR2), in a high‐grade serous ovarian cancer cell line (OV90). Experimental Approach: Human ovarian cancer tissues ( n = 1, 200) and nine human ovarian cancer cell lines were assessed for PAR2 expression. PAR2 signalling mechanisms leading to cell migration and invasion were dissected using cellular assays, western blots, CRISPR‐Cas9 gene knockouts, pharmacological inhibitors of PAR2 and downstream signalling proteins in OV90 cancer cells. Key Results: PAR2 was significantly overexpressed in clinical ovarian cancer tissues and in OV90 ovarian cancer cells. PAR2 agonists, an endogenous protease (trypsin) and a synthetic peptide (2f‐LIGRL‐NH2 ), induced migration and invasion of OV90 ovarian cancer cells through activating a combination of Gαq/11, Gα12/13 and β‐arrestin1/2, but not Gαs or Gαi . This novel cooperative rather than parallel signalling resulted in downstream serial activation of Src kinases, then transactivation of epidermal growth factor receptor (EGFR), followed by downstream MEK–ERK1/2–FOS/MYC/STAT3–COX2 signalling. Either a PAR2 antagonist (I‐191), CRISPR‐Cas9 gene knockouts (PAR2 or Gα proteins or β‐arrestin1/2), or inhibitors of each downstream protein attenuated human ovarian cancer cell motility. Conclusion and Implications: This study highlights a novel shared signalling cascade, requiring each of Gαq/11, Gα12/13 and β‐arrestin1/2 for PAR2‐induced ovarian cancer cell migration and invasion. This mechanism controlling a cellular function is unusual in not being linked to a specific individual G protein or β‐arrestin‐mediated signalling pathway.